Congenital Cholesteatoma Localized to the Mastoid Cavity and Presenting as a Mastoid Abscess - Salim M. Sloma Tabook; Hazem M. Abdel Tawab; Naveen Kumar Gopal (Case Reports in Otolaryngology)
Introduction. Congenital cholesteatoma is a pearly white mass that rarely originates from the mastoid process. Case Report. A 21-year-old male patient presented to our department with severe right mastoid pain and postauricular fluctuant swelling for 23 days. There was no preceding history of ear complaints and examination showed a normal right ear drum. Emergency exploration of the mastoid process was done on the same day and revealed localized cholesteatoma limited only to the mastoid cavity. Conclusion. Despite a rarity, the mastoid process should be always put in mind as a site of origin for congenital cholesteatoma.